URBAN GEOHERITAGE. THE SECULAR WELLS OF CRAIOVA, ROMANIA - Albă, Claudia-Daniela; Boengiu, Sandu (Quaestiones Geographicae, 2020)
The aim of this study is to highlight three of the urban geomorphosites of Craiova city, which can be promoted in a specific itinerary for geotourism or integrated, along with other objectives, in different touristic products. The selection of the three sites was made after analysing historical documents, images and maps, which show the landscape transformation, the development of the community and the settlement expansion. For the assessment of the sites, the method created by the University of Rome was used and two stages were performed: a) the geomorphological analysis by multitemporal and multidisciplinary approaches and b) the geomorphoheritage characterisation by calculating the VSGh index (Value of a Site for Geotourism index) based on the presence of five attributes. One of the three sites, The Valley of the 7 Wells, is nowadays an invisible geomorphosite with an important geotouristic and educational potential.